2016
DOI: 10.1155/2016/2325987
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on MAGE-C2 as a Potential Biomarker for Triple-Negative Breast Cancer

Abstract: Objective. In the current study, we measured the expression status of melanoma antigen gene c2 (MAGE-C2) in triple-negative breast cancer (TNBC) and analyzed its prognostic with the clinical pathological features of patients with TNBC. Methods. The expressions statuses of MAGE-C2 were detected in TNBC tissues and paracarcinoma tissues by immunohistochemistry, reverse transcription-polymerase chain reaction (RT-PCR), and western blotting. Then, we investigated the relationship of MAGE-C2 expression status and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…MAGE-C2 was abnormally expressed in non-small cell lung cancer and correlated with the prognosis [ 18 ]. MAGE-C2 could also serve as a biomarker for triple-negative breast cancer, TNBC [ 19 ]. Interestingly, MAGE-C2-specific TCRs could also affect cancer progression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAGE-C2 was abnormally expressed in non-small cell lung cancer and correlated with the prognosis [ 18 ]. MAGE-C2 could also serve as a biomarker for triple-negative breast cancer, TNBC [ 19 ]. Interestingly, MAGE-C2-specific TCRs could also affect cancer progression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collective studies support the notion that elevated MAGEC2 expression can be observed in different cancers19,20 and that MAGEC2 expression is correlated with several important clinicopathological attributes, including tumour size,21 TNM stage,8 and recurrence 22. Moreover, Zhao et al9 and Figueiredo et al8 described the prognostic role of MAGEC2 in breast cancer and larynx cancer, respectively. Our data are in accordance with the findings of these previous studies.…”
Section: Discussionmentioning
confidence: 82%
“…A high incidence of MAGEC2 expression has been reported in larynx squamous cell carcinoma and is remarkably correlated with an advanced clinical stage 8. A recent pilot study also reported that MAGEC2 could be a potential biomarker for triple-negative breast cancer 9. However, the detailed characteristics and mechanisms of MAGEC2 in HCC are inadequately understood.…”
Section: Introductionmentioning
confidence: 99%
“…MAGEC2 belongs to the MAGE family which codes for cancer-testis antigen. They are located on the X chromosome and involved in normal tissue development as well as in tumorigenesis of various tumors [ 38 , 39 ]. MAGEC2 expression is restricted to male germ cells and is not found in adult somatic cells.…”
Section: Introductionmentioning
confidence: 99%